Strategic Framework for Character IP Development Using Design Thinking and Transmedia Storytelling in Indonesia - Tengku Salwa Nabila Johan; Sonny Rustiadi (Program MM Universitas Surabaya, 2026)
Purpose: This research aims to develop a strategic framework to resolve the critical